Effect of Vitamin D Supplementation and Calcium in Reducing the Risk of Preeclampsia: Meta-Analysis - Fajriyani, Fanny Kartika; Pamungkasari, Eti Poncorini; Murti, Bhisma (Indonesian Journal of Medicine, 2020)
Background: Preeclampsia (PE) is a major complication in pregnancy and a major cause of maternal and fetal morbidity and mortality. Analysis of risk factors and prevention of preeclampsia are needed to reduce the adverse effects of preeclampsia. Important supplements during pregnancy to prevent the increase in blood pressure of pregnant women are Vitamin D and calcium. This study aimed to analyze the effect of vitamin D and calcium supplementation on reducing the risk of preeclampsia.Subjects and Method: This study is a meta-analysis of a number of randomized controlled trials. The articles used in this study were obtained from several databases including PubMed, Google Scholar, Springerlink, and Sciencedirect. The articles used in this study were those published from 2002-2020. The article search was carried out by considering the eligibility criteria defined using the PICO model. P: Pregnant women, I: vitamin D and calcium, C: placebo, and O: preeclampsia. The keywords to find articles are as follows: "Vitamin D" OR "Calcium" OR "Vitamin D and Calcium" AND "preeclampsia" AND "Randomized Controll Trials". The articles included in this study are full text articles with Cross-sectional study design. Articles were collected using PRISMA flow diagrams. Articles were analyzed using the Review Manager 5.3.Results: A total of 9 articles were reviewed in this study. The meta-analysis showed that vitamin D supplementation reduced the risk of preeclampsia in pregnant women (RR= 0.45, 95% CI 0.32-0.63, p<0.001). The meta-analysis of 8 articles also showed that calcium supplementation reduced the risk of preeclampsia in pregnant women with calcium (RR= 0.42; 95% CI= 0.31 - 0.57; p<0.001). This meta-analysis combines primary research from Iran, India, Bangladesh, South Africa, Cameroon, and Saudi Arabia.Conclusion: Vitamin D and calcium supplementation reduces the risk of preeclampsia.Keywords: vitamin D, Calcium, preeclampsia, randomized controlled trialCorrespondence: Fanny Kartika Fajriyani. Masters Program in Public Health, Universitas Sebelas Maret, Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: fannykfa9@gmail.com.Indonesian Journal of Medicine (2020), 05(04): 308-320https://doi.org/10.26911/theijmed.2020.05.04.06.